The Creation of the New Media Ecosystem in New York City: An Entrepreneurial Approach - Wymbs, Cliff (American Journal of Management, 2022)
The objective of this study was to further the understanding of entrepreneurship by disaggregating entrepreneurial activity into three distinct actors (freelancing, anti-institutional and institutional). Each of the entrepreneurial actors performs a different, but complimentary, role in a different phase of the creation and evolution of the new media ecosystem/cluster, so they warrant individual attention. The study of ecosystems is furthered by the identification of the dynamic relationships among entrepreneur actors and how their roles, and the relative importance of their roles, change over time. We know very little about how individual entrepreneurs actually transform the institutions that foster or preclude the creation of ecosystems, which makes it relatively hard to put theoretical insight into practice. A dialectic process model is used to analyze a historical case and gain insight into the processes of contestation and entrepreneurship that explain the emergence of a new ecosystem. The study highlights the importance of using a narrative approach to identify continuous change factors rather than the traditional comparative static approach to study network changes.